Effectiveness of KCL and KNO3 Fertilization on Growth and Results of Two Melon Varieties (Cucumis melo L.) - Rahmawati, Rina Fatimah; Istiqlal, Muhammad Ridha Alfarabi; Sugeru, Herik; Warip, Warip (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The demand for fruits in Indonesia continues to increase along with the increase in public consumption. Melon is one of the fruits that requires intensive handling in its cultivation because it is vulnerable to environmental changes and diseases. This study aims to determine the effectiveness of adding KCL and KNO3 fertilizers on the growth and yield of two melon varieties. This study used a non-factor randomized complete block design (RCBD). There were four treatments consisting of a combination of fertilizers and melon varieties, namely P1 (KCL and new madesta varieties), P2 (KNO3 and new madesta varieties), P3 (KNO3 and glamour varieties), P4 (KCL, KNO3 and new madesta varieties), with 6 replications so that there were 24 experimental units. The results showed that P3 treatment gave the best results in stem diameter, number of leaves, early flowering age, fruit weight and fruit diameter. P2 treatment gave the highest average yield on the parameters of fruit flesh thickness and total soluble solids (PTT). P3 treatment has the potential for further research, P3 treatment can fulfill the expected criteria with the highest fruit weight of most treatments. The provision of alternative K sources did not give a real response to melon plants, thus it would be more efficient to use K sources that are more economical in the melon cultivation system carried out.